KATA DAN MAKNA DALAM BAHASA MELAYU TERNATE - Betty Litamahuputty (Masyarakat Linguistik Indonesia, 2014)
Ternate Malay is one of the languages in which a word may fulfil various grammatical roles and express different meanings without showing any formal features on the word. Even if morphological processes are applied, they merely add something to the meaning and do not indicate grammatical features. It is the linguistic context as well as the nonlinguistic situation that determine how words and strings of words have to be interpreted to achieve the most suitable meaning. This article shows how certain function words, the word order, and additional prosodic features facilitate Ternate Malay speakers and hearers in expressing and interpreting strings of words. The examples are taken from spontaneous told narratives and display a kind of natural spoken Ternate Malay.